mtDNA data reveal disparate population structures and High Arctic colonization patterns in three intertidal invertebrates with contrasting life history traits - Csapó, Hedvig; Jabłońska, Aleksandra; Węsławski, Jan Marcin; Mieszkowska, Nova; Gantsevich, Michael; Dahl-Hansen, Ida; Renaud, Paul; Grabowski, Michał (Frontiers in Marine Science, 2023)
Introduction Post-glacial climate variation is known to have influenced the distribution of marine species in the North Atlantic. In particular, the Atlantic side of the Arctic has experienced strong fluctuations in both atmospheric and sea surface temperature, as well as seasonal ice coverage since the last glacial maximum (LGM). Here, we aim to unveil the phylogeography and historical demography of three rocky intertidal marine invertebrates showing a trans-Atlantic distribution and presently inhabiting the Arctic: Gammarus oceanicus, Littorina saxatilis and Semibalanus balanoides. Methods We used a large amount of mitochondrial DNA barcode data, both newly-obtained and stored in public databases. We performed phylogeographic and demographic analyses on 1119 G. oceanicus, 205 L. saxatilis, and 884 S. balanoides sequences. Results Our results show that all three of these boreal species have expanded their effective population sizes in the high Arctic Svalbard Archipelago since the LGM. Analyses investigating the origin of all these populations point to the eastern Atlantic. Discussion Based on our results we conclude that the expansion of these boreal species to the Arctic possibly happened during an earlier warm cycle of the Holocene era, and is probably not the result of the recent ‘Atlantification’ of the Arctic. We also discuss the effects of dispersal potential on population structure as an important aspect of comparative biogeographical studies.